Anisotropic toughening of nanotwin bundles in the heterogeneous nanostructured Cu. (15th April 2022) - Zhao, H.Z.; You, Z.S.; Tao, N.R.; Lu, L.
Abstract: In the first report [H.Z. Zhao, Z.S. You, N.R. Tao, L. Lu, Acta Mater. 210 (2021) 116830], anisotropic strengthening of nanotwin bundles in the heterogeneous nanostructured (HNS) Cu was investigated from the perspective of deformation compatibility. To further understand their toughening mechanism, the anisotropic fracture behaviors of this HNS Cu with preferentially oriented nanotwins and elongated nanograins are investigated in this paper. Depending on the orientations of the crack planes relative to the nanotwin bundles (or the alignment of elongated nanograins), the HNS Cu shows a distinctly anisotropic fracture behavior. When both the crack plane and crack growth direction are perpendicular to the nanotwin bundles, HNS Cu exhibits the highest fracture toughness ( J IC ), which is approximately three times higher than that of the case where both crack plane and crack growth direction are parallel to the nanotwin bundles. This orientation-dependent fracture toughness is attributed to the anisotropic toughening of the nanotwin bundles and the crack deflection caused by the elongated nanograins. Abstract : Image, graphical abstract